Rudolf Maister v slovenski književnosti - Bošnjak, Blanka (Studia Historica Slovenica, 2025)
This paper will present the figure of Rudolf Maestro in selected Slovenian literature, who is known in cultural memory mainly as a fighter for the northern Slovenian border, soldier, general, poet and bibliophile. The two novels selected for the discussion are Jože Hudales's The Eagle with Open Wings: a novel about General Rudolf Maister (1974) and The General: a novel about Rudolf Maister (1981). The aim of the present discussion is to demonstrate, through the method of interpretation and interpretive reading of the novels about Rudolf Maister, the use of intertextual strategies, namely allusions as references to figures from Slovenian literary history and literature, depicting real persons from the time of Maister's life, which serve the function of documenting the life story line of the greatness of this (cultural) saint.
Keywords: boj za severno mejo; canonization; cultural memory; developmental novel; fight for the northern Slovenian border; kanonizacija; kulturni spomin; Maister, Rudolf; moderna; modernity; razvojni roman; Slovene literature; slovenska književnost